Autoimmune and iodine deficiency diseases of the thyroid gland as the "tip of the iceberg" of multiple organ pathology - Ekaterina A. Troshina (Терапевтический архив)
The article presents modern data on the etiology, pathogenesis, diagnosis and treatment of autoimmune and iodine deficiency diseases in the context of possible associations with other autoimmune and non-autoimmune somatic pathologies. Diseases of the thyroid gland (TG) are presented in the form of a “signal pathology” that requires the attention of doctors; the issues of the syndrome of multiple autoimmune lesions are considered, an obligatory component of which is a disease of the TG, most often autoimmune. Data are provided on the possible relationship between autoimmune, iodine deficiency and tumor diseases of the TG from the point of view of common mechanisms of pathogenesis and mutual influences. Emphasis is placed on the clinical manifestations of thyrotoxicosis and hypothyroidism, their effects on the cardiovascular system, and their connection with the course of rheumatic and other diseases. The importance of personalizing the diagnosis of TG pathology and the mandatory exclusion of possible associated diseases is shown.